Promoting Class Peer Assessment in Engineering Education - Koh, Yit Yan (INTI International University, 2007)
The supportive statement to reduce rote learning in current education system from the Deputy Prime Minister of Malaysia in April pointed out a new direction in the current education development in this country. In light of this, the author’s faculty initiated pilot study of the Transformative Learning in three engineering classes during the May 2007 semester. The idea of this study is to implement the relatively new philosophy of learning into the current education system that switches the learning environment from Rote learning to understanding and from an Acceptance mindset to reconceptualization. Having been involved in the research of the study, the author has introduced the idea of Class Peer Assessment into the class activities in helping students to reconceptualise knowledge. This paper reports on the students perception on this idea and their performance with the implementation of the idea.